Conservative treatment protocol on horizontal radicular fractures of cervical third – Case report (Research, Society and Development, 2020)
Dental trauma has a significant occurrence in dentistry. Root fractures can be considered as polytrauma because they involve different types of tissue: dentin, cementum, pulp and periodontium. Objective: to show a conservative therapeutic protocol option in the treatment of horizontal root fractures in order to preserve the dental structure taking into account the patient's socioeconomic condition. Case report: a 15-year-old male patient went to the Dentistry Clinic of the Federal University of Alagoas where he sought care after suffering a trauma. On clinical examination, it was observed that the upper central incisor (11) had a cervical horizontal root fracture and slight palatal displacement. We opted for the installation of semi-rigid containment as immediate treatment. Subsequently, a cortical segment pulpectomy to the fracture line was performed with intracanal medication composed of calcium hydroxide and 2% chlorhexidine gel. After 2 weeks, the canal was filled with MTA. Conclusion: Endodontic treatment was successfully performed, its prognosis depends on the type of tissue repair in the fracture line and health of periodontal tissues.